Hair shaft, an overview for pediatric pathologists. - Galluzzo Mutti, M.L. (European Journal of Pediatric Dermatology, 2023)
The author starts with normal hair, mentioning the embryology, anatomy, physiology, the growth cycle, the two types – terminal and vellous – of hair, their pigmentation and shape, and the ways to examine them. She then talks about pigmentation anomalies, in particular gray hair syndromes. Structural anomalies – fractures, irregularities, rotation and torsion of the shaft – follow. Then it is the turn of diseases associated with hair anomalies – Menkes syndrome, Netherton syndrome, trichothiodistrophia, uncombable hair, moniletrix, pili annulati, woolly hair and associated syndromes, pseudonits, and Marie-Unna hereditary hypotrichosis –.